Rollout of a statewide Australian telestroke network including virtual reality training is associated with improved hyperacute stroke workflow metrics and thrombolysis rate - Garcia-Esperon, Carlos; Maltby, Steven; Butcher, Ken; Hasnain, Md Golam; Chew, Beng Lim Alvin; O'Brien, William; Evans, James W.; Ang, Timothy; Edwards, Leon; Blair, Christopher; Delcourt, Candice; Parsons, Mark W.; et al. (Frontiers in Stroke, 2024)
Background. Telestroke networks aim to address variability in both quality and access to stroke care in rural areas, by providing remote access to expert stroke neurologists. Implementation of telestroke requires adaptation of workflow processes and education. We previously developed virtual reality (VR) workflow training and documented acceptability, utility and feasibility. The effects on acute stroke treatment metrics have not been previously described. Aims. The overall aim was to improve hyperacute stroke metrics and shorten the time-to-reperfusion therapy administration in rural settings. Methods. This study applies a natural experiment approach, collecting stroke metric data during transition from a pre-existing pilot to a statewide telestroke service at 5 rural hospitals. Pre- and post-intervention data included baseline patient demographics and assessment, diagnosis and treatment delivery metrics. The primary study outcome was door-to-decision time (thrombolysis and endovascular thrombectomy). Secondary outcomes included door-to-computerized tomography time, door-to-thrombolysis time and proportion of patients receiving thrombolysis or thrombectomy treatment. Usage data relating to the VR stroke workflow training of interprofessional healthcare professionals was automatically captured via Wi-Fi. Statistical comparisons of clinical metrics between the pre- and post-intervention time periods, defined as the timeframes before and after VR deployment, were performed. Results. A total of 2683 patients were included (April 2013 - December 2022); 1910 pre- and 773 post-intervention. All acute stroke time metrics significantly improved post-intervention. The primary outcome, door-to-decision time, decreased from 80 minutes [56-118] to 54 minutes [40-76; P<.001]. Secondary outcomes also improved, including door-to-thrombolysis time (90 minutes [68-114] vs. 68.5 minutes [54-90]; P<.001) and proportion of patients thrombolysed (11% vs. 16%; P<.001). The proportion of patients transferred for thrombectomy was unchanged (6% vs. 7%; P=.69). Seventy VR sessions totalling 15 hours 39 minutes of training time were logged. VR training usage varied across sites (3 – 31 sessions per site). Conclusions. Delivery of a multi-factorial intervention including infrastructure, funding, education and training (with VR workflow training) as part of a state-wide telestroke rollout was associated with improved acute stroke treatment metrics. Additional work is required to identify the contribution of each intervention component on clinical outcomes and to increase training uptake and sustainment.